PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT DI DESA TIRTAWANGUNAN KECAMATAN SINDANGAGUNG KABUPATEN KUNINGAN PROVINSI JAWA BARAT - Endang Hermawan; Dini Pebriyani; Dwi Nurita Julianty; Futri Safitri; Galih Tri Laksono (Sekolah Tinggi Pariwisata Mataram, 2021)
Empowerment of village communities through village government is needed to develop the potential and capabilities of rural communities who are often marginalized. Therefore, the village government is required to develop and maximize human resources with various kinds of community empowerment programs specifically designed to raise the socio-economic welfare of rural communities, such as that of the Tirtawangunan Village Government, Sindangagung District, Kuningan Regency, West Java Province. The research data were collected through field studies and literature studies. The purpose of this research is to find out how community empowerment is carried out by the local village government. The results of this study indicate that the Tirtawangunan Village Government has implemented community empowerment maximally by allocating a budget for each community empowerment program even though obstacles remain in each program. The Tirtawangunan Village Administration has also collaborated with the private sector to drive any programs that involve the private sector so that the impact is felt by all Tirtawangunan Village residents